INTEGRATION OF TRI KAYA PARISUDHA VALUES IN THE DISCOVERY LEARNING MODEL IN ELEMENTARY SCHOOL STUDENTS' SCIENCE LEARNING - Ida Ayu Kade Citra Diwya Citta; Made Adi Nugraha Tristaningrat; Kadek Hengki Primayana (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
ABSTRACT Science learning in elementary schools not only focuses on understanding the material but also aims to develop critical thinking skills and shape students' character. However, classroom learning still largely relies on traditional methods, resulting in students' problem-solving abilities not being fully developed. This article discusses the application of the Tri Kaya Parisudha values ​​in the Discovery Learning model in science learning through a literature study method. The research was conducted by reviewing various scientific references related to the topic. The results of the study indicate that the Discovery Learning model can encourage students to be more active in discovering concepts independently, thereby improving critical thinking and problem-solving skills. Furthermore, the Tri Kaya Parisudha values ​​help shape positive attitudes in thinking, speaking, and acting in students. The combination of these two approaches results in learning that emphasizes not only academic abilities but also comprehensive character development. Therefore, this model is considered suitable for implementation in science learning in elementary schools. ABSTRAK Pembelajaran IPA di sekolah dasar tidak hanya berfokus pada pemahaman materi, tetapi juga bertujuan untuk mengembangkan kemampuan berpikir kritis serta membentuk karakter siswa. Namun, pembelajaran di kelas masih banyak yang bergantung pada metode tradisional, sehingga kemampuan pemecahan masalah siswa belum berkembang secara optimal. Artikel ini membahas penerapan nilai Tri Kaya Parisudha dalam model Discovery Learning pada pembelajaran IPA melalui metode studi literatur. Penelitian ini dilakukan dengan mengkaji berbagai referensi ilmiah yang relevan dengan topik tersebut. Hasil kajian menunjukkan bahwa model Discovery Learning dapat mendorong siswa untuk lebih aktif dalam menemukan konsep secara mandiri, sehingga meningkatkan kemampuan berpikir kritis dan pemecahan masalah. Selain itu, nilai Tri Kaya Parisudha membantu membentuk sikap positif dalam berpikir, berkata, dan bertindak pada diri siswa. Kombinasi kedua pendekatan ini menghasilkan pembelajaran yang tidak hanya menekankan kemampuan akademik, tetapi juga pengembangan karakter secara menyeluruh. Oleh karena itu, model ini dinilai sesuai untuk diterapkan dalam pembelajaran IPA di sekolah dasar.